Contamination of trichlorobenzene isomers in food: toxicity, analytical methods, occurrence in food, and risk assessments - Hyegyeong Lee; Kiyun Kim; Junhyeong Park; Joon-Goo Lee (Applied Biological Chemistry)
Abstract Trichlorobenzenes (TCBs), comprising the isomers 1,2,3-, 1,2,4-, and 1,3,5-TCB, disrupt metabolic processes by inducing liver enzymes involved in xenobiotic metabolism, suggesting a broad toxicological impact. Specifically, exposure to TCBs is associated with significant organ-specific toxicities, such as increased liver and kidney weights in rodents and cytotoxic effects in mammalian cells, which include DNA damage without metabolic activation. Used extensively in industrial and agricultural sectors, TCBs are prevalent pollutants in various ecosystems, including air, food, surface water, groundwater, sediment, soil, and sewage. This is a concern because of their tendency to accumulate in lipid-containing tissues of animals and humans and potentially serious risks to human health and ecosystems. Information showing the presence of TCBs in food, drinking water, and even human breast milk underscores the need for ongoing assessment of the extent of these contaminants in food to measure the potential exposure to these chemicals. TCBs are extracted from various food sample matrices, and then instrumental analysis is performed, typically gas chromatography (GC) coupled with a variety of detectors. This review discusses the occurrence and risk assessment of TCBs in foods, as well as the toxicology and analytical methods related to TCBs.